Primordial gravastar from inflation - Yu-Tong Wang; Jun Zhang; Yun-Song Piao (Physics Letters B, 2019)
The de Sitter (dS) bubbles can nucleate spontaneously during inflation, and will be stretched by the cosmological expansion to astrophysical scale. We report on a novel phenomenon that some of such bubbles might develop into the gravastar (the ultra-compact object with a dS core) after inflation, which witnessed the occurrence of inflation and might survive till today. It is pointed out that if such a primordial star was involved in one of the LIGO/Virgo events, the post-merger object will eventually collapse into a black hole. As a result, the late-time gravitational wave ringdown waveform will exhibit a series of “echoes” with intervals increasing with time.